Terremotos, mudanzas, reconstrucciones: lo que aprendimos en Lima (XVII-XVIII) - Scaletti-Cárdenas, Adriana (Pontificia Universidad Católica del Perú, 2022)
The earthquakes of the seventeenth and eighteenth centuries were decisive for Lima, the City of the Kings. From the perspective of the history of architecture, the moments after the earthquakes are particularly interesting, especially the reconstructions of the great viceregal capital. What was rebuilt and why? What materials and methods were chosen and for what reasons? Where and how were the new lots laid out? Why was the city not moved, as it happened in other similar cases? This paper reflects on these questions and on what the presence of such disasters meant in the evolution of Lima and Peruvian immovable material culture.

Los terremotos de los siglos XVII y XVIII fueron determinantes para Lima, la Ciudad de los Reyes. Desde la perspectiva de la historia de la arquitectura son particularmente interesantes los momentos posteriores a los sismos, sobre todo las reconstrucciones de la gran capital virreinal. ¿Qué se reconstruyó y por qué? ¿Qué materiales y métodos se eligieron y por qué razones? ¿Dónde y de qué forma se trazaron los nuevos solares? ¿Por qué no se mudó la ciudad de lugar, como sucedió en otros casos semejantes? Este trabajo reflexiona sobre estas preguntas y sobre lo que significó la presencia de tales desastres en la evolución de la cultura material inmueble limeña y peruana.
Earthquakes, moves, reconstructions: what we learned in Lima (XVII-XVIII)
Keywords: Earthquakes; Lima; Patrimony; Reconstruction; Terremotos; Lima; Patrimonio; Reconstrucción; https://purl.org/pe-repo/ocde/ford#6.00.00